2019
DOI: 10.3390/pr7040212
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Future Electricity Generation and Emissions Assessment for Pakistan

Abstract: Electricity demand in Pakistan has consistently increased in the past two decades. However, this demand is so far partially met due to insufficient supply, inefficient power plants, high transmission and distribution system losses, lack of effective planning efforts and due coordination. The existing electricity generation also largely depends on the imported fossil fuels, which is a huge burden on the national economy alongside causing colossal loss to the environment. It is also evident from existing governm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
(44 reference statements)
1
28
0
Order By: Relevance
“…The multiple regression analysis concluded that the model was valid and correctly specified and the renewables were significant indicators of low carbon levels in all 27 EU countries, since the values of the estimated coefficients of the regression model were significantly different than zero and most of the variation of CO 2 emissions in EU countries was explained by the model. The results of the paper confirm recent studies of renewable energy impact on low carbon levels [47][48][49][50][51][52][53]. In addition, the novelty of this study resides in the fresh outlook taken for a set of 27 EU countries for the period 2008-2017, in order to assess the interaction between renewables and CO 2 emissions.…”
Section: Discussionsupporting
confidence: 79%
“…The multiple regression analysis concluded that the model was valid and correctly specified and the renewables were significant indicators of low carbon levels in all 27 EU countries, since the values of the estimated coefficients of the regression model were significantly different than zero and most of the variation of CO 2 emissions in EU countries was explained by the model. The results of the paper confirm recent studies of renewable energy impact on low carbon levels [47][48][49][50][51][52][53]. In addition, the novelty of this study resides in the fresh outlook taken for a set of 27 EU countries for the period 2008-2017, in order to assess the interaction between renewables and CO 2 emissions.…”
Section: Discussionsupporting
confidence: 79%
“…The increased emissions of greenhouse gases (GHGs), such as carbon dioxide (CO 2 ), methane (CH 4 ), ozone, and nitrous oxide, are causing severe damage to the global environment. Among other greenhouse gases, CO 2 emissions are considered as the principal cause of global warming, thereby toppling the climate [1][2][3]. The CO 2 emissions due to excessive burning of fossil fuels, such as coal, oil, and gas, along with increased deforestation, have considerably contributed to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…This situation has prompted the consideration and research on the measures to reduce CO 2 emissions. One of the key measures to reduce CO 2 emissions is to reduce fossil fuel consumption and maintain economic growth by meeting part of the energy needs by harnessing renewable energy sources [3]. In order to substantiate this measure, the literature has sufficiently maintained the establishment of relationships among renewable energy production, CO 2 emissions, and economic growth [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, various prediction models developed in the literature to predict the electricity usage as per country wise. For instance, scholars attempted to predict the future electricity emission and its generation in Pakistan (Mengal et al, 2019). However, energy production in India is quite different as the growth of the energy sector and the installation of hydro and electricity plants reduces the load.…”
Section: Related Workmentioning
confidence: 99%